The Impact of Government Social Media Information Quality on Public Panic During the Infodemic - Zhai, Shanshan; Li, Yuanxiang John; Chi, Maomao (Frontiers in Psychology, 2022)
The COVID-19 pandemic triggered the first global “Infodemic” in the era of social media. Understanding the ways in which governments deal with negative impacts of the infodemic (e.g, public panic) has become a priority. This paper uses the theoretical framework of the Elaboration Likelihood Model (ELM) to explore mechanisms for alleviating panic associated with the infodemic. It considers, in particular, the quality of information circulated on Government Social Media (GSM) as the central route, and local government trust as the peripheral route. An empirical study was conducted using data froma focus group interview and a questionnaire survey collected within the first three weeks following the citywide lockdown of Wuhan, China. The results show that: (1) Quality of GSM information does not significantly reduce public panic, but local government trust significantly increases people’s pandemic prevention knowledge; (2) Pandemic prevention knowledge is a critical mediator between information quality of GSM and public panic, as well as local government trust and public panic; (3) Information quality of GSM significantly increases people’s trust in local governments. This paper contributes to the literature on infodemic and government’s social media, and provides implications for practice.